Providensia Allah dalam Kitab Ayub - Subekti, Tri (Sekolah Tinggi Teologia Kerusso Indonesia, 2022)
Abstract: God tests a person's faith through problems that come repeatedly in life. God is sovereign and incontrol of every human life, history, existence and order of the universe. God's extraordinaryinvolvement in human life, especially in the book of Job, is in the form of providence or God's careand provision for Job. The book of Job discusses how Job experienced God's extraordinaryprovidence in his life and family. The author uses the literature study method to describe the form ofGod's providence in the book of Job. Through literature studies by reading books, the author canformulate a useful view of the existence of God in the book of Job